Estimating nutrient uptake requirements for radish in China based on QUEFTS model - Zhang, Jiajia; He, Ping; Ding, Wencheng; Xu, Xinpeng; Ullah, Sami; Abbas, Tanveer; Ai, Chao; Li, Mingyue; Cui, Rongzong; Jin, Chongwei; Zhou, Wei (Scientific reports, 2019)
Imbalanced fertilization has caused lower yield and nutrient use efficiency for radish ( Raphanus sativus L.) production in China. Estimating nutrient requirements for radish is crucial in optimizing fertilization to resolve the problem. On-farm experiments in the radish-growing regions of China from 2000 to 2017 were collected to investigate the relationship between fleshy root yield and nutrient accumulation in radish plant using the Quantitative Evaluation of the Fertility of Tropical Soils (QUEFTS) model. The QUEFTS model predicted a linear increase in fleshy root yield if nutrients were taken up in balanced amounts until yield reached about 60%–70% of the potential yield. The balanced N, P, and K requirements in radish plant simulated by the QUEFTS model were 2.15, 0.45, and 2.58 kg to produce 1000 kg of fleshy root, and the corresponding internal efficiencies (IEs, kg fleshy root per kg nutrient in total plant dry matter) for N, P, and K were 465.1, 2222.2, and 387.1 kg kg −1 . The simulated balanced N, P, and K removal by fleshy root to produce 1000 kg fleshy root were 1.34, 0.30, and 1.93 kg, respectively. Approximately 62%, 67%, and 75% of N, P, and K in radish plant were presented in the fleshy root and removed from the soil. Field validation experiments confirmed the consistency between the observed and simulated nutrient uptake values. The QUEFTS model was proven to be effective for estimating nutrient requirements of radish and will contribute to develop fertilizer recommendations for radish cultivated in China.